Comparative analysis of circular and triangular gold nanodisks for field enhancement applications - COSTA, Karlo Queiroz da (2013)
In this paper, we present a quantitative comparison of circular and triangular gold nanodisks with the same length and thickness. The method of moments is used to solve numerically the scattering problem. With this model, we investigate the spatial near field distribution, spectral response, far field diagrams, and bandwidth wavelength of these particles. Our results show that the resonant wavelength and the near field enhancement and confinement of the triangular particle are larger than those for the circular particle, but the resonance bandwidth and scattering cross section of the triangular particle are smaller.